From Sumak Kawsay to Living Well debate: Signified in dispute and dispute for signifiers - Vásquez Bustamante, Juan Pablo; Orellana Yáñez, José; Rodrigues Teixeira, Juliane (Instituto de Estudios Internacionales, 2021)
The Buen Vivir (Living Well) notion has been set out as the Amazonic Kichwa philosophical principle’s representation in Spanish for Sumak Kawsay. From its incorporation to the Constitution of the Republic of Ecuador as a model of society and reality horizon, this concept has generated an intense political and academic debate between different ways of interpretation and understanding. According to this problem phenomenon, this paper sets out Living Well as a signifier, which is a permanent-disputing political object because of its significance and appropriation. A documentary analysis of primary and secondary sources, and an analysis and synthesis work to three proposals for typologies that fit these debates are carried out. This work analyzes and arranges the field in dispute into four discourse currents or groups that –according to its interests, perspectives and paradigmatic frames– dispute the Living Well significance and appropriation.